Rape Myth Acceptance Among Lesbian, Gay, Bisexual, and Mostly Heterosexual College Students - Worthen, Meredith Gwynne Fair (Journal of interpersonal violence, 2021)
Although there is a wealth of existing research on various correlates and patterns of rape myth acceptance (RMA), including how RMA relates to homophobia (i.e., antigay and antilesbian perspectives) and negativity toward lesbian, gay, and bisexual (LGB) men and women rape victims, no research to date has specifically focused on RMA among LGB and “mostly heterosexual” men and women. The current study examines how gender, sexual identity, personal experiences with rape (i.e., knowing/being a survivor), feminist identity, patriarchal gender norms, attitudes toward lesbian, gay, bisexual, and transgender (LGBT) people, and the interactions among these relate to LGB college students’ (n = 389; 24% gay/lesbian, 19% bisexual, 57% mostly heterosexual) RMA using the Illinois Rape Myth Acceptance Scale–Short Form. Findings show that being a woman, being LGB, identifying as a feminist, and knowing/being a survivor are all negatively related to RMA, whereas patriarchal gender norms are positively related to RMA. Attitudes toward LGBT people had differing effects whereby attitudes toward gay men were unassociated with RMA, attitudes toward lesbian women and trans men were negatively associated with RMA, and attitudes toward bisexual men and women and trans women differed depending on the comparison reference group (exclusive heterosexuals, n = 1,551, mostly heterosexuals, n = 222). Furthermore, the interacting effects of these identities, experiences, and perspectives also revealed significant findings that add complexity to these relationships. Overall, this research seeks to fill the gaps in the literature, expand our knowledge about rape myths, and contribute to new lines of inquiry that focus on LGB people’s perspectives to work toward a deeper understanding of rape myths, so that ultimately, these damaging perspectives can be dispelled.